Assessing Quality of Pharmacist-Led Education for Patients with COPD Using the Lung Information Needs Questionnaire: A Pilot Study - Teri Alisha Barnett; Anastasia Jenkins; Alicia Bouldin; Melvin Crumby; Alice Kelly Morgan; Michael Warren (University of Minnesota Libraries Publishing, 2019)
Background: Transitioning a patient from the hospital to home is an area of vulnerability for patients with Chronic Obstructive Pulmonary Disease (COPD).  Patients with COPD frequently readmit as they often do not understand their disease state, medications or when to seek medical attention. Objectives: The objective of this study is to determine the impact that pharmacist-led education has on a patient's understanding of their disease state by assessing the results of the Lung Information Needs Questionnaire (LINQ). Methods:  This study uses a quasi-experimental design to formally assess pharmacist-led education provided to patients with COPD using the LINQ. The LINQ was used to assess knowledge of the disease state and medications before and after receiving education on disease state management, smoking cessation and proper medication use.   Results: A total of 17 patients completed the LINQ. The survey results showed a statistically significant improvement in patient understanding in 4 of the 6 targeted areas. Conclusion: Results from the formal assessment using the LINQ suggest that pharmacist-lead education for COPD patients is beneficial and reliable. This study presents a continued need for patient education and research in this high-risk patient population.   Article Type: Original Research